PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2021 -2023 - Wa Ode Debi Yustisia; La Ode Turi; Nichen Nichen (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of leverage and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This study uses a quantitative approach. The data used are secondary data obtained from the financial statements of manufacturing companies listed on the IDX for the 2021-2023 period. The analytical method used is multiple linear regression analysis using SPSS Version 23. The findings indicate that leverage does not have a substantial impact on company value, as evidenced by a significance value of 0.599 (>0.05). Profitability significantly influences Firm Value, as indicated by a significance value of 0.000 (<0.05). Both Leverage and Profitability substantially affect Firm Value, as evidenced by a significance value of 0.000 (<0.05). An R value of 0.979 signifies a robust positive correlation between the independent variables (Leverage and Profitability) and the dependent variable (Firm Value). This means that the independent variables have a correlation of 97.9% with Firm Value. The R-square value of 0.959 indicates that Profitability contributes 95.9% to the variance of Company Value, and the remaining 4.1% is due to external variables